2021
DOI: 10.24945/mvf.01.21.1866-0533.2299
|View full text |Cite
|
Sign up to set email alerts
|

Körperliche Aktivität in der SARS-CoV-2-Pandemie: Selektiver Überblick und Perspektiven

Abstract: Das SARS-CoV-2-Virus sowie die Maßnahmen zur Vermeidung von dessen Ausbreitung verändern die Rahmenbedingungen für körperliche Aktivität bzw. Bewegung. Vor dem Hintergrund ihrer gesundheitsfördernden Wirkung stellt sich die Frage, ob und wie sich das Bewegungsverhalten der Bevölkerung oder einzelner Gruppen in Deutschland während des Lockdowns verändert, welche Korrelate es aufweist, und wie es sich fördern lässt. Mitglieder der DNVF-Arbeitsgruppe Bewegungsbezogene Versorgungsforschung wurden gebeten, Einblick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Gardening and cycling showed clear seasonal differences with higher popularity in spring and summer. Therefore, both served as alternatives to sports activities mainly during the 1 st LD, which has been observed in other studies as well [12,39]. Gardening for example showed a significant, moderate effect during the study course: it was done 30 minutes more per week in April/May 2020 than in the following year, when the 2 nd LD was ending and first restrictions were eased.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Gardening and cycling showed clear seasonal differences with higher popularity in spring and summer. Therefore, both served as alternatives to sports activities mainly during the 1 st LD, which has been observed in other studies as well [12,39]. Gardening for example showed a significant, moderate effect during the study course: it was done 30 minutes more per week in April/May 2020 than in the following year, when the 2 nd LD was ending and first restrictions were eased.…”
Section: Discussionsupporting
confidence: 60%
“…doing home repair work, which was insufficiently reported as activity in the MLTPAQ. This argumentation is supported by several studies that observed an incline in moderate PA and walking in leisure time during the pandemic [12,[39][40][41]. This might have positively influenced muscle strength of the low TIG.…”
Section: Plos Onementioning
confidence: 59%